The effect of nutrient limitation on bacterial wax ester production - Martin, LK; Huang, WE; Thompson, IP (Elsevier, 2023)
Nutrient limitation is widely employed to alter the behaviour of micro-organisms. Here, the impact of nitrogen and, for the first time, phosphate limitation is investigated on the production of bacterial storage lipids; specifically wax esters, a class of storage lipids of industrial interest, by the bacterium Acinetobacter baylyi ADP1 grown on the low-cost substrate acetate. Studies determined the absolute and temporal effects of nutrient limitation and identified a maximum wax titre of 132 mg/L and content of 17 % of biomass. A 4-fold increase in wax production was achievable by manipulating carbon: phosphate ratio. Multivariable analysis identified a novel interaction effect between carbon: nitrogen and carbon: phosphate ratios on wax production. Extreme phosphate starvation shifted the dominant lipid class from wax esters to triacylglycerols, the first report of the potential of phosphate limitation to alter the type of lipid generated. These findings offer valuable insights for future microbial bioproduction studies.